Exploring Financial and ESG Drivers of Firm Value: The Moderating Effect of Dividend Policy in the Energy Sector - Sartono, Imam; Risman, Asep (Dinasti Publisher, 2025)
The transition toward sustainable energy practices has created increasing pressure on companies to align financial performance with environmental, social, and governance (ESG) objectives. This study aims to examine the effects of sustainability, profitability, and capital structure on firm value, while analyzing the moderating role of dividend policy among energy sector companies listed on the Indonesia Stock Exchange (IDX). Sustainability is assessed using ESG Score, profitability by Return on Assets (ROA), capital structure by Debt to Equity Ratio (DER), and dividend policy by Dividend Payout Ratio (DPR). A quantitative method is employed, utilizing panel data from 28 firms selected through purposive sampling over the 2017–2023 period. The findings reveal that profitability and capital structure significantly influence firm value, while sustainability shows no significant effect. Furthermore, dividend policy negatively moderates the relationship between profitability and firm value, but does not moderate the effect of sustainability or capital structure. The study concludes that financial metrics remain dominant drivers of firm value in the energy sector, while ESG initiatives may require longer-term adoption to show measurable impact. These insights offer practical implications for corporate managers and investors in aligning strategic financial decisions with sustainability goals.